Altitude features of spruce decline on the north-eastern megaslope of Ukrainian Carpathians - Oliinyk, V. S.; Zeinalian, A. M. (Forestry and Forest Melioration, 2020)
Introduction Nowadays the problem of spruce decline is urgent for the Carpathians as European spruce (Picea abies (L) H. Karst.) is the main forest-forming species there. Researchers have thoroughly studied the causes and prevalence of this phenomenon. However, a number of aspects of spruce decline require a quantitative assessment. It is particularly relevant for the indicators in high-altitude forest zones, relief features and forestry situations. Materials and Methods The decline processes were studied based on indicators of three forestries in the basin of the river Bystrytsia Solotvynska, covering the whole spectrum of altitude zonation of the north-eastern megaslope of the Carpathians, ranging from fir-beech forests on the foothills to high mountain spruce forests. The analysis involved 376 plots allocated to continuous and selective sanitary felling in secondary drying spruce stands in different altitude zones. The main characteristics of the spruce decline are the quantity and areas of this phenomenon with its division into partial and continuous. A distribution of the spruce drying was also analyzed depending on the exposure of steep slopes in the mountains and landscape and forestry situations on the foothills. Results The main abiotic factor influencing the spread of spruce decline in the region is the height above sea level. Thus, here the dominant partial drying increases from the foothill fir-beech forests to the mountain beech-fir belt, and then it decreases at the hypsometric levels of beech-fir-spruce forests and mitigates in the upper spruce zone. The continuous type of drying evenly, in small extent, increases with increasing height. In general, spruce trees are most vulnerable to drying at altitudes of 400–900 m above the sea level, which involves 87% of their foci and 84% of the total area with drying spruce. In general, an average area of ??drying foci varies from 1.8–2.8 ha (altitude of 300 m) to 4–4.2 ha (altitude of 600–800 m) and then it decreases to 1.0 ha (altitude of 1200–1300 m). The dependence of partial and continuous decline on the height of the terrain is inverse, parabolic with correlation relations ? 0.83. The continuous drying is characterized by a rectilinear dependence on the height with a correlation coefficient of 0.80. It has been found that a decline area is affected to a small extent by the exposure of mountain slopes. For example, the average and maximum areas of ??partial drying are 4.1 and 17.5 hectares respectively on the southern slopes and 3.7 and 16.7 hectares on the northern slopes, Thus, the decline areas are 5–10% larger in insolated sites than in the shady slopes. In flattened foothill, decrease in stability of the forest is influenced by other regularities relate to the conditions of the laid down relief. Here the decline area depends on the landscape and forestry features. The decline processes are at their minimum level in the depth of the forests. There is a slight increase in areas bordering openings, felling sites, and young stands, while the most severe decline occurs at the edges. Conclusions The distribution of decline of secondary spruce stands depends on the altitude, relief and local features of the region. In mountainous conditions, this process increases in the range of altitudes of 400–-900 m above the sea level. Decline processes gradually decrease on higher slopes. On the northern slopes, decline area is slightly smaller than on the south ones. On the foothills, decline is influenced by the forestry specificities, particularly by the proximity to open areas. 3 Tables, 11 Refs. Key words: high-altitude forest zones, secondary stands, altitude, slope exposure.